On the early fate of hydrothermal iron at deep‐sea vents: A reassessment after in situ filtration. Issue 9 (9th May 2017) - Waeles, M.; Cotte, L.; Pernet‐Coudrier, B.; Chavagnac, V.; Cathalot, C.; Leleu, T.; Laës‐Huon, A.; Perhirin, A.; Riso, R. D.; Sarradin, P.‐M.
Abstract: Deep‐sea hydrothermal venting is now recognized as a major source of iron (Fe), an essential trace element that controls marine productivity. However, the reactions occurring during dispersal from buoyant plumes to neutrally buoyant hydrothermal plumes are still poorly constrained. Here we report for the first time on the dissolved‐particulate partition of Fe after in situ filtration at the early stage of mixing at different hydrothermal discharges, i.e., Lucky Strike (37°N), TAG (26°N), and Snakepit (23°N) on the Mid‐Atlantic Ridge. We found that hydrothermal iron is almost completely preserved (>90%) in the dissolved fraction, arguing for low iron‐bearing sulfide precipitation of iron in basalt‐hosted systems with low Fe:H2 S ratios. This result can only be explained by a kinetically limited formation of pyrite. The small part of Fe being precipitated as sulfides in the mixing gradient (<10%) is restricted to the inclusion of Fe in minerals of high Cu and Zn content. We also show that secondary venting is a source of Fe‐depleted hydrothermal solutions. These results provide new constrains on Fe fluxes from hydrothermal venting.